On Fekete-Szegö Problems for Certain Subclasses Defined by q-Derivative - Huda Aldweby; Maslina Darus (Journal of Function Spaces)
We derive the Fekete-Szegö theorem for new subclasses of analytic functions which are q-analogue of well-known classes introduced before.